Credibility and the Dynamics of Stabilization Policy : A Basic Framework - Calvo, Guillermo (IMF Working Papers; Working Paper, 1990)
This paper studies price stabilization policy under both predetermined and flexible exchange rates. Under predetermined exchange rates, a non-credible stabilization program results in an initial expansion of output, followed by a later recession. The initial expansion accompanies an appreciating real exchange rate. Under flexible exchange rates, the recession occurs at the beginning of the program. The real exchange rate appreciates sharply on impact but depreciates afterwards. Lack of credibility is more costly under predetermined exchange rates because the real effects are more pronounced.